Application of Basophil Activation Test with Anthraxin for Laboratory ( in vitro) Diagnostics of Anthrax - A. N. Kulichenko; E. L. Rakitina; D. G. Ponomarenko; O. V. Logvinenko; A. G. Ryazanova (Проблемы особо опасных инфекций, 2012)
Demonstrated is the possibility to use in vitro basophil activation test with anthraxin, with registration of the results by means of flow cytometry, for anthrax diagnostics. This approach seems promising as it provides quantitative assessment of sensitization of the organism and does not cause its additional allergization. The duration of the analysis is 1h. The test is suggested for application, as an express one, for early and retrospective laboratory diagnostics of anthrax, estimation of post-vaccinal immunity.